General Microbiology - Hans G. Schlegel
his revised, up-dated and expanded edition of Professor Schlegel?s well-established textbook provides an excellent introduction to microbiology for a wide range of undergraduate students. This new edition includes new species, new phylogenetic relationships and a greater emphasis on environmental and ecological matters, whilst retaining the traditional strengths of the previous edition.